Tailored nanotopography of photocurable composites for control of cell migration. Issue 8 (21st January 2021) - Hasselmann, Sebastian; Kopittke, Caroline; Götz, Maria; Witzel, Patrick; Riffel, Jacqueline; Heinrich, Doris
Abstract : Influencing amoeboid cell migration by a novel approach creating tailored surface roughness via a photocurable composite material. Abstract : External mechanical stimuli represent elementary signals for living cells to adapt to their adjacent environment. These signals range from bulk material properties down to nanoscopic surface topography and trigger cell behaviour. Here, we present a novel approach to generate tailored surface roughnesses in the nanometer range to tune surface properties by particle size and volume ratio. Time-resolved local mean-squared displacement (LMSD) analysis of amoeboid cell migration reveals that nanorough surfaces alter effectively cell migration velocities and the active cell migration phases. Since the UV curable composite material is easy to fabricate and can be structured via different light based processes, it is possible to generate hierarchical 3D cell scaffolds for tissue engineering or lab-on-a-chip applications with adjustable surface roughness in the nanometre range.